2008
DOI: 10.1111/j.1468-2389.2008.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Multisource Assessments of Behavioral Competencies and Selection Interview Performance

Abstract: This study sought to determine whether and how ratings of leadership in a developmental multisource feedback program compare against those obtained by leadership selection decision makers. Seventy-seven senior managers received feedback on eight competencies that also formed the basis of a subsequent promotional interview for senior executive positions. Each rating source displayed a unique perspective on the participants, but only the supervisor and peer ratings predicted performance on the interview. As well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…It may turn out that constructs tend to be somewhat variable and job specific. Conversely, it is possible that a general performance factor exists for interviewees, much like the one that has been found for employee performance (Darr & Catano, 2008; Viswesvaran, Schmidt, & Ones, 2005). However, to facilitate analysis of construct specificity, it would be helpful to understand the major sources of influence on interview constructs and their overall level of association across interviews.…”
Section: Interview Constructsmentioning
confidence: 99%
“…It may turn out that constructs tend to be somewhat variable and job specific. Conversely, it is possible that a general performance factor exists for interviewees, much like the one that has been found for employee performance (Darr & Catano, 2008; Viswesvaran, Schmidt, & Ones, 2005). However, to facilitate analysis of construct specificity, it would be helpful to understand the major sources of influence on interview constructs and their overall level of association across interviews.…”
Section: Interview Constructsmentioning
confidence: 99%
“…Before great faith can be placed in multi‐source appraisals, it is important to determine whether these appraisals are prone to personal biases. Research on multi‐source ratings has found only modest agreement among sources in their appraisals of a focal person (Darr & Catano, 2008; Harris & Schaubroeck, 1988; Smither, London, & Reilly, 2005). Plus, differences in appraiser ratings have been found to be stable across time and across appraisal instruments (Nilsen & Campbell, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both studies did not examine the prediction of supervisor ratings of OCB, but peer-ratings of OCB. In contrast to this approach, employees' performance in the selection context is most frequently assessed via supervisor ratings (Woehr and Roch, 2012), and supervisor ratings have shown to be the best single predictors of independent performance criteria when compared to self-and peer-ratings (Atkins & Wood, 2002;Darr & Catano, 2008).…”
Section: Structured Interviews As Predictor Methodsmentioning
confidence: 99%